Xanthine Oxidoreductase Reference Values in Platelet-Poor Plasma and Platelets in Healthy Volunteers. (20th January 2015) - Cecerska-Heryć, Elżbieta; Jesionowska, Anna; Klaudyna, Szupiluk; Katarzyna, Siewierska; Dominika, Mączka; Dominika, Pawlak; Marta, Urbańska; Dołęgowska, Barbara
Abstract : Introduction. Xanthine oxidoreductase (XOR) is an enzyme belonging to the class of hydroxylases. XOR is stated, inter alia, in the kidneys, liver, and small intestine as well as in leukocytes and platelets and endothelial cells of capillaries. Its main role is to participate in the conversion of hypoxanthine to xanthine and the uric acid. It occurs in two isoforms: dehydrogenase (XD) and oxidase (XO), which is considered one of the sources of reactive oxygen species. Aim of the Study. Determination of reference values of xanthine oxidoreductase activity in PPP and platelets. Materials and Methods. Study group consisted of 70 healthy volunteers. The isoform activities of xanthine oxidoreductase were determined by kinetic spectrophotometry. Results. A statistically significant difference between the activity of the XOR in PPP and platelets (P < 0.001 ). The highest activity of XO was found in both PPP and blood platelets. Significant differences between the activity of the various isoforms in PPP (P = 0.0032 ) and platelets (P < 0.001 ) were also found. Conclusions. The healthy volunteers showed the highest activity XO (prooxidant) and the lowest XD (antioxidant), which indicates a slight oxidative stress and confirmed physiological effects of XOR.